IMPLIKASI KEBIJAKAN PEMBATASAN IMPOR HORTIKULTURA INDONESIA PASCA PENANDATANGANAN PREFERENTIAL TRADE AGREEMENT (PTA) DENGAN PAKISTAN TAHUN 2012 - Haq, Nurul; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The objectives of the study were to analyze the implication of horticultural import control policy for oranges producers and consumers in Indonesia, after PTA between Pakistan and Indonesia was signed in 2012. Under PTA, Indonesia offered market accessing to Pakistani kinnow at 0% tariff, which is expected to significantly enhance the export of this product. But in the same year, to protect the domestic horticulture farmers, the government of Indonesia had established an import control policy, released by the Ministry of Agriculture (MOA).This research used a qualitative research methods that the datas were taken from books, journals, newspapers, iinternet and the previous studies that had datas which relevant with the title. By using neo mercantilism perspective and protectionisme theory wiil explain the direction of object of analysis.The result of the study were the Indonesia horticultural import control policy has a positive effect to orange producers and consumers in Indonesia. For the orange’s producers, the implementations of horticultura import control policy made increasing orange production, farmer exchange rate, and local orange image. Then, for the orange consumers made increasing food security, avaibility of product, and quality of orange.Keywords: Horticultura import policy, Non Tariff Barrier, Preferential Trade Agreement